The Relationship Between Decisional Regret and Well-Being in Patients With and Without Depressive Disorders: Mediating Role of Shared Decision-Making - Xu, Richard Huan; Zhou, Ling-ming; Wang, Dong (Frontiers in Psychiatry, 2021)
Purpose The objectives of this study were twofold: (1) to assess the relationship between patients’ decisional regret and their well-being, and (2) to examine the mediated effect of shared decision-making (SDM) on this relationship. Methods A cross-sectional survey was conducted in five cities in Southern China. Patients were asked to fill out questionnaires assessing their decisional regret, SDM, subjective well-being, and depressive status. Mediation analysis was used to investigate the effect of SDM on the relationship between patients’ decisional regret and their subjective well-being. Results The findings showed significant direct negative effects of decisional regret on subjective well-being and SDM. For non-depressive patients, SDM exerted a significant and indirect effect on reducing the negative influence of decisional regret on subjective well-being. Conclusions Findings suggest that implement SDM can decrease patients’ decisional regret and improve their wellbeing, however, there is a need to examine their depressive status as part of routine healthcare.